2002
DOI: 10.1021/ja003169l
|View full text |Cite
|
Sign up to set email alerts
|

Electron−Nuclear Double Resonance Spectroscopic Evidence for a Hydroxo-Bridge Nucleophile Involved in Catalysis by a Dinuclear Hydrolase

Abstract: Despite the current availability of several crystal structures of purple acid phosphatases, to date there is no direct evidence for solvent-derived ligands occupying terminal positions in the active enzyme. This is of central importance, because catalysis has been shown to proceed through the direct attack on a metal-bound phosphate ester by a metal-activated solvent-derived moiety, which has been proposed to be either (i) a hydroxide ligand terminally bound to the ferric center or (ii) a bridging hydroxide. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 57 publications
6
91
0
Order By: Relevance
“…Alternatively, pK es1 could be assigned to the deprotonation of a terminal Fe(III)-bound water molecule. However, the absence of this water ligand in resting Uf [13] make this assignment less likely. Also, the significant change of pK es1 upon replacing Fe(II) [40].…”
Section: Kinetic Properties Of Fe(iii)ni(ii)-ufmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, pK es1 could be assigned to the deprotonation of a terminal Fe(III)-bound water molecule. However, the absence of this water ligand in resting Uf [13] make this assignment less likely. Also, the significant change of pK es1 upon replacing Fe(II) [40].…”
Section: Kinetic Properties Of Fe(iii)ni(ii)-ufmentioning
confidence: 99%
“…The divalent metal ion is coordinated to the oxygen atom of the bridging aspartate, the nitrogen atoms of two histidine residues and an asparagine oxygen atom. On the basis of recent spectroscopic and crystallographic data, the Fe(III) in the resting state is five-coordinate, including a bridging (hydr)oxo ligand; the M(II) site is likely to be six-coordinate with a terminal water molecule completing its first coordination sphere [13]. The enzyme thus provides an asymmetric binuclear active site with an NO 4 Fe(III) site and an N 2 O 4 divalent metal site (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…9,79 However, the observation (by ENDOR) that no terminal Fe(III)-bound hydroxide group may be present in the resting state of pig PAP argues against this (although the possibility that substrate binding may promote the binding of a water molecule to Fe(III) cannot be ruled out at present). 86 It could also be shown that fluoride can replace the bridging hydroxide group in pig PAP. 99 Upon the further addition of phosphate, a ternary PAP‚F‚PO 4 complex was formed, where phosphate binds to both metal ions, as observed in the crystal structure of pig PAP.…”
Section: Catalytic Mechanismmentioning
confidence: 99%
“…6). As far as the interdimer interactions (J 23 = J 3 and J 14 = J 2 ) are concerned, these could not be a priori considered equal, due to the proton localization on one of the bridging oxides, and the subsequent asymmetry of the interdimer bridges [Fe(1)-O(16)-Fe(4) = 146.81 (21) • , Fe(2)-O(8)-Fe(3) = 144.00 (22) • ]. Thus, to test whether these are indeed equal, initial fitting attempts considering J 2 = J 3 were carried out.…”
Section: Magnetic Susceptibilitymentioning
confidence: 99%